Between walls: Analysis of deaths from Covid-19 in the Brazilian prison system in 2020 - Chaves, Edna Maria Camelo; dos Santos, Isabel Freitas; Melo, Mariane Menezes; da Silva, Cicero Jordan Rodrigues Sobreira; de Almeida, Paulo César; Moreira , Thereza Maria Magalhães; Torres , Raymond Augusto Martins (Seven Editora, 2023)
Objective: The objective of this study is to analyze the number of cases and deaths from COVID-19 in the Brazilian prison system in 2020.  Methodology: This is an observational, analytical and ecologically designed study of COVID-19 deaths in the Brazilian prison system in Apr/Dec/2020. Data were collected from epidemiological bulletins at the National Council of Justice website. As a unit of analysis, the number of confirmed cases and deaths from COVID-19 were selected for the months of exposure to SARS-CoV-2, in the regions of Brazil and Federative Units in the year 2020.  Correlation analysis and linear regression of the COVID-19 lethality percentage per month were performed. Results: In the year 2020 the total number of confirmed cases of COVID-19 through RT-PCR testing and rapid testing in persons deprived of liberty was 41,971, including the two cases from the Federal Prison System. The total number of deaths was 129. The case fatality rate decreased every month and the Southeast region presented a higher number of reported cases and deaths. Final thoughts: The pandemic due to the novel coronavirus has played a revealing role in the unsanitary and inhumane conditions of the Brazilian prison system. It is believed that from the panorama of the pandemic in the prison system in the year 2020, they can subsidize comparative studies of the subsequent years.DOI:https://doi.org/10.56238/emerrelcovid19-043